Determinants of consumer behaviour in novice markets: the case of wine. Issue 1 (13th July 2015) - Capitello, Roberta; Agnoli, Lara; Begalli, Diego
Abstract : Purpose: – This study aims to understand the behaviour of novice consumers and provide businesses with guidelines regarding how to approach the different typologies of novice consumers from new inexperienced markets and from new generations. Design/methodology/approach: – The reasoned action approach is applied to wine consumer, and two parallel surveys using a questionnaire have been conducted with a sample of the Missouri population – representing new consumers – and a sample of the young Italian population – representing young consumers located in traditional consuming countries. Two research hypotheses are tested. Findings: – The hypothesis testing reveals two effects. The age effect creates similarities in the decision-making process structure, and attitude and subjective norm have the same weight in influencing behavioural intention. The novice effect creates differences in the structure; however, similarities exist at a more basic level than that of attitude and subjective norm, in salient beliefs and salient referents. Practical implications: – The study highlights that penetration of these consumer segments should pursue different marketing approaches: educational goals for young people from new markets, an experiential marketing approach to improve the link between product and producer for new consumers and emphasis on cultural aspects of the product in a "young manner" for young consumers from traditional consuming markets. Originality/value: – For the first time in the literature, this study analyses commonalities and peculiarities in the decision-making process of novice consumers.